Dinamika Elite Lokal Madura - Zamroni, M. Imam (UI Scholars Hub, 2012)
The priyayi played a vital role in leading the Indonesian community during the colonial era. The same applies to Madura society. During the colonial era, power wielded by the priyayi was constricted on the basis of Madura culture and was strengthened by the bureaucratic power structure at both the village and district/ city level. This was manifested in such ways as serving as a klébun or bupati. However, the pattern of priyayi power, which was underpinned by feudalism waned, being replaced by Islamic religious leaders known as kiai. During the New Order regime, kiai in Madura played a very dominant role which was not only limited to the realm of religion, but also all aspects of life ranging from social, politics, economic, to culture. Nevertheless, with the dawn of the reformation era, economic elites have catapulted themselves to prominence, and there are growing signs that they are replacing the role which religious leaders used to play in Madura society in general and in the political domain in particular through forming shadow state as a tool used to exert control over Madura Political dynamics. This concise paper presents as discussion of ‘political fights’ among cultural, religious, bureaucratic, and economic elites in Madura.